MoS2/NiO hybridized with reduced graphene oxide for glycerol and sorbitol electrooxidation - Mohammad Bagher Askari; Sadegh Azizi; Mohammad Taghi Tourchi Moghadam; Parisa Salarizadeh (Electrochemistry Communications)
Using glycerol and sorbitol as fuels in fuel cells has received limited attention in the literature. This study presents the synthesis of a composite material comprising molybdenum disulfide (MoS₂) and nickel oxide (NiO) via a hydrothermal method, which was subsequently hybridized with reduced graphene oxide (RGO) to enhance its catalytic performance. The catalytic activity of the MoS₂/NiO/RGO composite for the oxidation of glycerol and sorbitol was systematically evaluated. The results demonstrated exceptional catalytic activity, with the current density of 311 mA/cm2 at 0.5 V for MoS₂/NiO/RGO catalyst during glycerol oxidation reaction (GOR). Furthermore, the catalyst exhibited remarkable stability, maintaining 86.6 % of its activity after 5 h of chronoamperometric analysis in the glycerol oxidation reaction. In the case of the sorbitol oxidation reaction (SOR), the MoS₂/NiO/RGO composite delivered impressive results, achieving 205 mA/cm2 at 0.51 V and a stability of 90.2 %. This research is promising for introducing cost-effective, durable, and efficient catalysts to oxidize alternative fuels, with potential applications in fuel cell anodes.